EDIBLE PORTION KARKAS, KADAR LEMAK DAN KOLESTEROL DAGING DOMBA DENGAN IMBANGAN AMPAS BIR DAN RUMPUT GAJAH YANG BERBEDA - Agus Priyono; Imbang Haryoko (Udayana University, 2016)
The research was aimed to evaluated edible portion meat and as an effort to improve the quality of lamb meat. (low content of saturated fatty acids and cholesterol), with brewery waste. The research used 16 four months old local rams with body weight 5-10 kgs. The feed composition used was Pennisetum purpureum grass, rice bran, beer solid waste, salt and minerals mix. The research used experimental method in vivo for 150 days using Completely Randomized Design with four treatments. Each treatment was with four repetition. Treatment rations were R1=12% brewery waste: 48 % grass; R2 = 24% brewery waste: 36% grass; R3= 36% brewery waste: 24% grass; R4= 48 % brewery waste: 12% grass. The variables measured were : edible portion of carcass (%) (carcass weight, edible meat proximal and edible meat distal); the fat content of meat, meat and liver cholesterol of lamb meat. The results showed that the treatment significantly affect (P<0.05) to the percentage of edible meat distal, but not significantly terhadapa levels of fat and cholesterol lamb. Conclusion of the research that the balance 48% brewery waste: 12% of elephant grass can be used as a mixture of lamb feed without disrupting the activity of the physiology and metabolism of lamb Keywords : solid waste of beer, edible portion meat, cholesterol